Interventional pain management procedure for treating low back pain: anaesthesiologists should come forward - Sardar, K; Sultana, R; Das, G; Kapoor, V; Mahta, P; Rahman, Khalilur (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
DOI: http://dx.doi.org/10.3329/jbsa.v24i1.19796 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(1): 23-27